Experimental study of the influence of changes in load direction on the performance of a crown bearing - Costa, Lucrécio (2000)
Laboratory tests have been carried out in order to investigate the influence of small changes in load direction on the performance of a steadily loaded hydrodynamic crown journal bearing. Hydrodynamic pressures, temperature distribution in the bush internal surface, shaft temperature, oil flow rate and bush torque were measured for fixed sets of operating conditions, at three different groove locations with respect to load line (0º, -30º, +30º). For each groove location quantitative information is provided concerning the influence of applied load and shaft rotational speed on the performance characteristics. Changing the location of the groove around load line did affect flow rate and bush torque, but had only a slight or moderate effect on bush maximum temperature.